Zakat Management Model Through Organizational Network and Digital Marketing by LAZISNU Jember Regency - Abdul Hamid; Abdul Rokhim; Munir Is'adi (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2025)
This research is motivated by the significant potential of Zakat, Infaq, and Shadaqah (ZIS) in Jember Regency and LAZISNU Jember's efforts to optimize collection through innovative organizational network-based management and the use of digital marketing. Challenges faced include low public trust in zakat institutions and unequal digital literacy. The purpose of this study is to analyze the zakat management model implemented by LAZISNU Jember Regency through the integration of organizational networks and digital marketing. This study used a qualitative approach, with data collection methods including interviews, observation, and documentation. The results show that LAZISNU Jember implements a hybrid management model that combines the strength of NU's solid organizational network from the PCNU, MWC, to the Branch level with a digital marketing strategy through social media such as Instagram, Facebook, and TikTok. This model has proven effective in increasing fundraising, transparency, and donor outreach. However, the main obstacle faced is unequal digital literacy among administrators and some members of the community. The study recommends enhancing digital training for administrators to strengthen sustainability in zakat management.